A quad-band compact diversity antenna for GPS L1/Wi-Fi/LTE2500/WiMAX/ HIPERLAN1 applications - Singh H.S.; Agarwal M.; Pandey G.K.; Meshram M.K. (My University, 2025)
In this letter, a low-profile quad-band antenna array for multiple-input-multiple-output (MIMO) application has been presented. The proposed two-antenna array operates at GPS L1/Bluetooth/Wi-Fi/LTE2500/WiMAX/ HIPERLAN1 frequency bands. Each antenna element has an area of 25 × 10 mm2 over a small ground plane of the size 100 × 60 mm 2. To maintain the small size of the antenna element, folded patch is used. A rectangular slot is etched on the main radiator to utilize the higher-order mode. A quarter-wavelength resonator is integrated at the edge of folded patch to get an additional resonance for quad-band operation. An antenna prototype is fabricated, and measured results are in good agreement with simulated results. Radiation characteristics and diversity performance of the proposed structure are presented. © 2002-2011 IEEE.